Comparative Studies on Conventional and Ultrasound-Assisted Synthesis of Novel Homoallylic Alcohol Derivatives Linked to Sulfonyl Dibenzene Moiety in Aqueous Media - Mohamed F. Mady; Ahmed A. El-Kateb; Ibrahim F. Zeid; Kåre B. Jørgensen (Journal of Chemistry)
Novel homoallylic alcohols incorporating sulfone moieties were synthesized by the treatment of different carbonyl compounds with allylic bromides in aqueous media via sonochemical Barbier-type reaction conditions. Sulfonation of α-bromoketones with sodium benzenesulfinate in presence of CuI/2,6-lutidine rapidly gave β-keto-sulfones in good yields. In general, ultrasound irradiation offered the advantages of high yields, short reaction times, and simplicity compared to the conventional methods. The structures of all the compounds were confirmed by analytical and spectral data.